Pemodelan Dan Pengembangan Sistem Pendeteksian Penyakit Infeksi Tropis Berbasis Ontologi - Lalu Mutawalli (LPPM STMIK Lombok, 2018)
Infection disease have been national or international problem. The prevalence rate of meaning is high for death. Infection disease difficulties to controlling. The occurrence of inequality ratio medical professionals is one of the things that became lack of control of infection disease. Information technology is needed to support the achievement of control, it became the base for building a modeling system that can detect the presence of infection disease, especially infectious disease with tropical infection categories. Ontology as a concept in building a system with using jaccard similarity method for calculation of the case. The result a system accuracy in this study, typhoid fever disease as much as 88%, dengue fever as much as 96% and malaria disease as much as 77%. System can be able to use by paramedic as reference the beginning for anamneses also patients can be able to use as an early warning to determine the condition health.